MENIMBANG EFEKTIFITAS PELATIHAN MODEL BLENDED LEARNING SELAMA PANDEMI COVID-19 - Muhammad Miftakhul Falah (Balai Diklat Keagamaan Bandung, 2023)
The purpose of this study is to evaluate the efficacy of training using an integrated learning model during the Covivirus-19 pandemic. This study consists of both qualitative and quantitative evaluation methods. The three stages of Kirkpatrick's evaluation model, reaction, learning, and behavior, are used to measure participant responses, learning outcomes, and behavioral changes following multimedia-based learning media training in Karanganyar's workplace. Participants numbered forty in the research based on the saturated sample technique. Positive sentiments (mean score of 4.4 /extremely high) dominated the responses of the participants to the training, which included widyaiswara, the committee, participation, and the facilities. The consistency of respondents' responses and the grade of items are both satisfactory. There is an effect of multimedia-based learning media training activities on participants' knowledge. Medium N Gain attained by 0.4285. The complexity aspect is the most difficult skill evaluation item, while the suitability of the material content is the easiest. Aspects that arise involve confidence, responsibility, activity, cooperation, neatness, discipline, originality, gratitude, honesty, courtesy, and initiative emerge. The level of behavior modification is determined by the effect of media on the learning process, the use of learning media intensity during the covid pandemic, and the relevance to competency development needs.Keywords: Kirkpatrick evaluation model; learning media; multimedia; blended learning